An Examination of Uncertainty in Perinatal Palliative Care - Bishop, Christine Elizabeth (Wake Forest University, 2015)
Medical ethics is a field that blends ethical theory with practice in a very concrete way. Many commonly discussed ethical issues derive specifically from addressing medical care at the end of life, and these issues become particularly complicated when the patient in question is a neonate or a woman carrying a fetus. Providing palliative and end-of-life care for these patients requires a complex interaction of clinical skills, communication skills, and ethical evaluation. This thesis is based on a practicum in which I observed discussions between health care professionals and parents about ethical issues in the care of perinatal and neonatal patients
Keywords: accompaniment; neonatology; pediatric palliative care; perinatal palliative care; uncertainty